Global analysis of erythroid cells redox status reveals the involvement of Prdx1 and Prdx2 in the severity of beta thalassemia - Romanello, Karen S.; Teixeira, Karina K.L.; Silva, João Pedro M.O.; Nagamatsu, Sheila T.; Bezerra, Marcos André C.; Domingos, Igor F.; Martins, Diego A.P.; Araujo, Aderson S.; Lanaro, Carolina; Breyer, Carlos A. [UNESP]; Ferreira, Regiane A.; Franco-Penteado, Carla; et al. (Public Library of Science (PLoS), 2018)
β-thalassemia is a worldwide distributed monogenic red cell disorder, characterized by an absent or reduced beta globin chain synthesis. The unbalance of alpha-gamma chain and the presence of pathological free iron promote severe oxidative damage, playing crucial a role in erythrocyte hemolysis, exacerbating ineffective erythropoiesis and decreasing the lifespan of red blood cells (RBC). Catalase, glutathione peroxidase and peroxiredoxins act together to protect RBCs from hydrogen peroxide insult. Among them, peroxiredoxins stand out for their overall abundance and reactivity. In RBCs, Prdx2 is the third most abundant protein, although Prdxs 1 and 6 isoforms are also found in lower amounts. Despite the importance of these enzymes, Prdx1 and Prdx2 may have their peroxidase activity inactivated by hyperoxidation at high hydroperoxide concentrations, which also promotes the molecular chaperone activity of these proteins. Some studies have demonstrated the importance of Prdx1 and Prdx2 for the development and maintenance of erythrocytes in hemolytic anemia. Now, we performed a global analysis comparatively evaluating the expression profile of several antioxidant enzymes and their physiological reducing agents in patients with beta thalassemia intermedia (BTI) and healthy individuals. Furthermore, increased levels of ROS were observed not only in RBC, but also in neutrophils and mononuclear cells of BTI patients. The level of transcripts and the protein content of Prx1 were increased in reticulocyte and RBCs of BTI patients and the protein content was also found to be higher when compared to beta thalassemia major (BTM), suggesting that this peroxidase could cooperate with Prx2 in the removal of H 2 O 2 . Furthermore, Prdx2 production is highly increased in RBCs of BTM patients that present high amounts of hyperoxidized species. A significant increase in the content of Trx1, Srx1 and Sod1 in RBCs of BTI patients suggested protective roles for these enzymes in BTI patients. Finally, the upregulation of Nrf2 and Keap1 transcription factors found in BTI patients may be involved in the regulation of the antioxidant enzymes analyzed in this work.